2013
DOI: 10.1186/1471-2377-13-32
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of plasma VEGF value in ischemic stroke - research for biomarkers in ischemic stroke (REBIOS) study

Abstract: BackgroundVascular endothelial growth factor (VEGF) is a well-known molecule mediating neuronal survival and angiogenesis. However, its clinical significance in ischemic stroke is still controversial. The goal of this study was to examine the temporal profile of plasma VEGF value and its clinical significance in ischemic stroke with taking its subtypes into consideration.MethodsWe prospectively enrolled 171 patients with ischemic stroke and age- and gender-matched healthy subjects. The stroke patients were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 23 publications
7
82
0
2
Order By: Relevance
“…Notably, VEGF-A has been associated with an increased risk of ischaemic stroke in the Framingham Heart Study 27 28. Studies of acute stroke have shown increased plasma VEGF-A levels at the time of stroke events and correlations between VEGF-A and worse long-term prognosis 29. In contrast to VEGF-D and AF-related stroke, the pathophysiological mechanisms for the association between VEGF-A and stroke are most likely different and could possibly be explained by hypoxia-induced expression of VEGF-A 29…”
Section: Discussionmentioning
confidence: 99%
“…Notably, VEGF-A has been associated with an increased risk of ischaemic stroke in the Framingham Heart Study 27 28. Studies of acute stroke have shown increased plasma VEGF-A levels at the time of stroke events and correlations between VEGF-A and worse long-term prognosis 29. In contrast to VEGF-D and AF-related stroke, the pathophysiological mechanisms for the association between VEGF-A and stroke are most likely different and could possibly be explained by hypoxia-induced expression of VEGF-A 29…”
Section: Discussionmentioning
confidence: 99%
“…Research by Matsuo et al argued that higher VEGF levels in atherothrombotic stroke, therefore, were associated with better outcomes than the low levels of VEGF in post-acute thrombotic stroke. Further, the research found that high levels of VEGF in embolic stroke were associated with worse outcomes 16. In this current study, evaluation of patients’ clinical conditions was not performed.…”
Section: Discussionmentioning
confidence: 82%
“…It has been observed that transplantation of bone marrow mesenchymal stem cells into ischemic brain resulted in gain of coordinated function in rats due to bone marrow cell soluble factor release, resulting in inhibited scar formation, increased angiogenesis and neuronal commitment [44,45]. Matsuo et al [46] posited that increased plasma VEGF values last for at least 90 days in all stroke subtypes, and the clinical significance varies for different stroke types. It was found that the severely affected group had a high mean VEGF of 592.1 versus 487.6 pg/ml (p = 0.76), without any statistically significant improvement between groups 1 and 2 (fig.…”
Section: Discussionmentioning
confidence: 99%